AMD TREATMENT USING MODIFIED SISAL/CHITOSAN NANOCOMPOSITE AS AN ADSORBENT - GS PERRY, W NHETA, ER SADIKU, MS ONYANGO (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study evaluates the ability of a sisal–chitosan microcomposite (SC) to remove Cr⁶⁺ and Mn²⁺ from acid mine drainage (AMD). Experimental conditions that influence adsorption performance were systematically examined. An optimal dosage of 1.5 g of SC produced the best metal removal. The SC3 formulation achieved the highest performance, reaching a maximum adsorption capacity of approximately 200 mg/g at 25°C, with an average metal removal efficiency of 97%. Adsorption of both metals was exothermic, with peak uptake at pH 2.0. EDX analysis confirmed attachment of metal ions to the composite surface.